Composite magnetically soft alloy powder and preparation method and application thereof

By combining the nano-doped metal with micro-ferroalloy powder and passing it through passivation treatment, the problem of poor performance of soft magnetic powder core in the prior art is solved, and a magnetic powder core preparation with high magnetic permeability and low magnetic loss is achieved. Performance and environmentally friendly process.

CN119480415APending Publication Date: 2025-02-18HENGDIAN GRP DMEGC MAGNETICS CO LTD +1

Patent Information

Application Number
CN202411728824.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

It is difficult to effectively prepare soft magnetic powder cores with high magnetic permeability and low magnetic loss in the prior art, and problems of agglomeration, uneven electroplating and uneven coating are prone to occur during the preparation process, resulting in poor performance.

Method used

By combining the nano-doped metal with micro-ferroalloy powder, drying and heat treatment under gentle conditions to form a composite soft magnetic alloy magnetic powder and passivating it to prepare a magnetic powder core with high magnetic permeability and low magnetic loss .

Benefits of technology

It achieves high magnetic permeability and low magnetic loss performance, has excellent superposition effect and good mechanical strength, and is simple in process, low equipment requirements and low environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005159804580000121
    Figure BDA0005159804580000121
  • Figure BDA0005159804580000131
    Figure BDA0005159804580000131
Patent Text Reader

Abstract

The invention provides composite magnetically soft alloy powder and a preparation method and application thereof, and the preparation method comprises the following steps: (1) mixing iron alloy powder, a doped metal source and a first solvent, carrying out one-step drying treatment to obtain a mixed dry material, and carrying out heat treatment on the mixed dry material to obtain a composite material; (2) mixing the composite material, a passivating agent and a second solvent, and performing two-step drying treatment to obtain composite magnetically soft alloy powder; wherein the doped metal source comprises colloidal metal and / or a metal simple substance, and the melting point of the metal simple substance is less than or equal to 800 DEG C.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of magnetic materials and relates to a composite soft magnetic alloy powder and a preparation method and application thereof. Background Art

[0002] Soft magnetic alloy powder has the advantages of high magnetic permeability, low loss, high saturation magnetic induction intensity, etc. It is mainly used to prepare magnetic cores and inductors and has a mature preparation and molding process. At present, my country's magnetic powder core products are at the world's leading level, and magnetic powder core products have been widely used in energy storage, home appliances, servers, 5G communications, photovoltaic power generation and other fields.

[0003] Metal soft magnetic powder core is a metal composite material mainly composed of ferromagnetic powder, which is coated with an insulating medium and then pressed. It has the advantages of high operating frequency, wide frequency application range, high magnetic permeability, low loss, high DC bias, etc. It can meet the application needs of current electronic components and has become a hot spot in material research at home and abroad.

[0004] The research on the performance of magnetic powder core materials mainly focuses on several directions such as high-frequency magnetic permeability, loss reduction, and improvement of DC superposition characteristics. Traditional insulation processes mainly use organic coating, inorganic coating, phosphating treatment and other technologies to reduce the loss of magnetic powder cores. Organic coating usually uses epoxy resin, silicone resin and other materials as the main coating agents, but it is easy to cause metal powder agglomeration, resulting in a decrease in resistance after heat treatment. Inorganic coating prepares magnetic powder by coating nano-oxides or phosphates on the surface of magnetic powder, but inorganic insulation auxiliary materials are easy to agglomerate, the cost is high, and the density is difficult to control, which affects the insulation of magnetic powder.

[0005] CN103545074A discloses a method for preparing a magnetic metal powder with a three-layer core-shell structure. The method uses a magnetic metal or alloy as the core, attaches a metal film on the surface through an electroplating process, and coats the outer layer with a metal oxide or nitride having insulating properties, and finally obtains a magnetic powder with a composite structure. Agglomeration and uneven electroplating are prone to occur during the preparation of the method, and the outermost insulating layer is difficult to adhere to the surface of the magnetic powder, and the coating is uneven, so it is difficult to form an ideal three-layer core-shell structure powder.

[0006] CN114582616A discloses a composite iron powder core with a layered structure, wherein the method prepares flaky powder by ball-milling iron powder and iron silicon, and then coats the powder with silicone resin, and then prepares the magnetic core by cold pressing. The magnetic powder prepared by the preparation method cannot effectively coat the silicone resin, which easily leads to extremely low resistance and poor density of the magnetic core, and the stacking state of the magnetic powder cannot be controlled during the pressing process.

[0007] CN116013631A discloses a method for preparing a FeSiAl composite soft magnetic powder core, which is to coat FeSiAl powder with an alumina insulating layer, a magnetic metal layer and silicon dioxide by aluminothermic method, thereby improving the performance of the magnetic powder. The preparation method is easily affected by the agglomeration of magnetic metal oxides, resulting in uneven coating of the magnetic powder after the aluminothermic reaction, and the composition ratio of the FeSiAl powder is easily changed, resulting in performance degradation.

[0008] The soft magnetic powder or magnetic core obtained by the method described in the above scheme has low stability and poor performance, and is difficult to be applied in practice. Summary of the invention

[0009] The purpose of the present invention is to provide a composite soft magnetic alloy powder and a preparation method and application thereof. The present invention composites nano-doped metal and micron ferroalloy powder to form a composite soft magnetic alloy magnetic powder. The magnetic powder core prepared using the composite soft magnetic alloy magnetic powder has high magnetic permeability and relatively low magnetic loss, better superposition effect, and good comprehensive performance.

[0010] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0011] In a first aspect, the present invention provides a method for preparing a composite soft magnetic alloy powder, the preparation method comprising the following steps:

[0012] (1) mixing an iron alloy powder, a doping metal source and a first solvent, performing a drying step to obtain a mixed dry material, and heat treating the mixed dry material to obtain a composite material;

[0013] (2) mixing the composite material, the passivating agent and the second solvent, and performing a two-step drying process to obtain a composite soft magnetic alloy powder;

[0014] Wherein, the doped metal source includes colloidal metal and / or metal element, and the melting point of the metal element is ≤800°C.

[0015] The present invention uses a doping metal source with a low melting point. If the melting point of a single substance of a metal element in the doping metal source is too high, i.e., >800°C, a colloidal metal containing the metal element is used, mixed with a ferroalloy powder in liquid phase, dried, and then heat treated. The molten nanometer-scale doping metal source is coated on the surface of the micrometer-scale ferroalloy powder to form a composite magnetic powder. The composite magnetic powder is then passivated to passivate the doping metal source on the surface of a portion of the ferroalloy powder, so that the composite soft magnetic alloy powder has high magnetic permeability, high frequency and low loss performance characteristics, higher DC superposition characteristics, and better mechanical strength.

[0016] The preparation process of the composite soft magnetic alloy powder of the present invention is simple and easy to implement, has low requirements on production equipment, and has little environmental pollution.

[0017] Preferably, the ferroalloy powder in step (1) comprises any one of iron-nickel alloy powder, iron-silicon alloy powder, iron-nickel-molybdenum alloy powder or iron-silicon-chromium alloy powder, or a combination of at least two thereof. Typical but non-limiting combinations include a combination of iron-nickel-molybdenum alloy powder and iron-silicon-chromium alloy powder, a combination of nickel alloy powder and iron-silicon-chromium alloy powder, or a combination of nickel alloy powder and iron-nickel-molybdenum alloy powder.

[0018] Preferably, the median particle size D50 of the ferroalloy powder in step (1) is 1 μm to 3 μm, for example, 1 μm, 1.5 μm, 2 μm, 2.5 μm or 3 μm, etc., and is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0019] Preferably, in step (1), the first solvent comprises acetone and / or ethanol.

[0020] Preferably, the mass ratio of the ferroalloy powder, the doping metal source and the first solvent in step (1) is 100:(0.2-0.8):20, for example: 100:0.2:20, 100:0.3:20, 100:0.5:20, 100:0.6:20 or 100:0.8:20, etc., not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0021] Preferably, the colloidal metal includes colloidal nickel and / or colloidal copper.

[0022] Preferably, the metal element includes any one of elemental zinc, elemental aluminum or elemental magnesium, or a combination of at least two of them.

[0023] Preferably, the metal element is nanometer-scale metal element powder.

[0024] Preferably, the temperature of the one-step drying treatment in step (1) is 100°C to 150°C, for example, 100°C, 110°C, 120°C, 130°C, 140°C or 150°C, etc., not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0025] Preferably, the drying time in step (1) is 10 min to 30 min, for example, 10 min, 15 min, 20 min, 25 min or 30 min, etc., not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0026] Preferably, the drying process in step (1) is followed by screening.

[0027] Preferably, the mesh size of the sieve used in the sieving process in step (1) is 200-500 mesh, for example, 200 mesh, 250 mesh, 300 mesh, 400 mesh or 500 mesh, etc., and is not limited to the listed values. Other values ​​not listed within the numerical range are also applicable.

[0028] Preferably, the temperature of the heat treatment in step (1) is greater than the melting point of the doping metal source.

[0029] Preferably, the temperature of the heat treatment in step (1) is less than the melting point of the ferroalloy powder.

[0030] Preferably, the atmosphere of the heat treatment in step (1) comprises nitrogen and / or hydrogen.

[0031] Preferably, the heating rate of the heat treatment in step (1) is 0.5°C / min to 2°C / min, for example, 0.5°C / min, 0.8°C / min, 1°C / min, 1.5°C / min or 2°C / min, etc., and is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0032] Preferably, the holding time of the heat treatment in step (1) is 1 h to 3 h, for example, 1 h, 1.5 h, 2 h, 2.5 h or 3 h, etc., and is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0033] Preferably, the median particle size D50 of the composite material in step (2) is 10 μm to 30 μm, for example, 10 μm, 15 μm, 20 μm, 25 μm or 30 μm, etc., and is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0034] Preferably, the passivating agent in step (2) comprises phosphoric acid and / or chromic acid.

[0035] Preferably, the mass ratio of the composite material to the passivating agent in step (2) is 100:(0.1-0.8), for example: 100:0.1, 100:0.2, 100:0.5, 100:0.6 or 100:0.8, etc., not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0036] Preferably, in step (2), the second solvent comprises acetone and / or ethanol.

[0037] Preferably, the temperature of the second-step drying treatment in step (2) is 100°C to 150°C, for example, 100°C, 110°C, 120°C, 130°C, 140°C or 150°C, etc., not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0038] Preferably, the time for the two-step drying treatment in step (2) is 10 min to 30 min, for example, 10 min, 15 min, 20 min, 25 min or 30 min, etc., not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0039] Preferably, the two-step drying process in step (2) is followed by screening.

[0040] Preferably, the mesh size of the sieve used in the sieving process in step (2) is 100 to 300 meshes, for example, 100 mesh, 150 mesh, 200 mesh, 250 mesh or 300 mesh, etc., and is not limited to the listed values. Other values ​​not listed within the numerical range are also applicable.

[0041] In a second aspect, the present invention provides a composite soft magnetic alloy powder, which is prepared by the preparation method described in the first aspect.

[0042] In a third aspect, the present invention provides a composite magnetic powder core, wherein the composite magnetic powder core comprises the composite soft magnetic alloy powder as described in the second aspect.

[0043] The magnetic powder core prepared by using the composite soft magnetic alloy powder of the present invention has a higher green body density, high magnetic permeability performance, and the characteristics of low magnetic core loss at high frequency.

[0044] In a fourth aspect, the present invention provides a method for preparing the composite magnetic powder core as described in the third aspect, the preparation method comprising the following steps:

[0045] The composite soft magnetic alloy powder as described in the second aspect is mixed with a coupling agent and then dried, the dried material is mixed with a binder and a release agent to obtain a mixed material, the mixed material is pressed to obtain a magnetic core blank, and the magnetic core blank is annealed to obtain the composite magnetic powder core.

[0046] Preferably, the coupling agent includes a silane coupling agent and / or a titanate coupling agent.

[0047] Preferably, the mass ratio of the composite soft magnetic alloy powder to the coupling agent is 100:(1-2), for example: 100:1, 100:1.2, 100:1.5, 100:1.8 or 100:2, etc., not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0048] Preferably, the drying temperature is 80°C to 150°C, for example, 80°C, 90°C, 100°C, 120°C or 150°C, etc., and is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0049] Preferably, the drying time is 10 min to 20 min, for example, 10 min, 12 min, 15 min, 18 min or 20 min, etc., and is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0050] Preferably, a screening process is performed after the drying.

[0051] Preferably, the mesh size of the sieve for the one-time screening process is 100-300 mesh, for example, 100 mesh, 150 mesh, 200 mesh, 250 mesh or 300 mesh, etc., not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0052] Preferably, the adhesive includes any one of epoxy resin, silicone resin or phenolic resin, or a combination of at least two of them.

[0053] Preferably, based on the mass of the dried material as 100%, the added amount of the binder is 1.5% to 3%, for example: 1.5%, 1.8%, 2%, 2.5% or 3%, etc., not limited to the listed values, other unlisted values ​​within the numerical range are also applicable.

[0054] Preferably, the release agent includes any one of zinc stearate, barium stearate, aluminum stearate, talc or boron nitride, or a combination of at least two thereof.

[0055] Preferably, based on the mass of the dried material as 100%, the added amount of the demoulding machine is 0.3% to 3%, for example: 0.3%, 0.5%, 1%, 2% or 3%, etc., not limited to the listed values, other unlisted values ​​within the numerical range are also applicable.

[0056] Preferably, the mixed material is subjected to a secondary screening process.

[0057] Preferably, the mesh size of the secondary screening treatment is 50-100 mesh, for example: 50 mesh, 60 mesh, 80 mesh, 90 mesh or 100 mesh, etc., not limited to the listed values, other values ​​not listed within the numerical range are also applicable.

[0058] Preferably, the pressure of the pressing treatment is 9T / cm 2 ~20T / cm 2 , for example: 9T / cm 2 , 10T / cm 2 , 12T / cm 2 , 15T / cm 2 or 20T / cm 2 The present invention is not limited to the numerical values ​​listed, and other numerical values ​​not listed within the numerical range are also applicable.

[0059] Preferably, the holding time of the pressing treatment is 1s to 10s, for example, 1s, 2s, 5s, 8s or 10s, etc., and is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0060] Preferably, the atmosphere of the annealing treatment includes nitrogen.

[0061] Preferably, the annealing temperature is 500-1100°C, for example, 500°C, 600°C, 800°C, 900°C or 1100°C, etc., but is not limited to the listed values, and other values ​​not listed within the range are also applicable.

[0062] Preferably, the heating rate of the annealing treatment is 0.5°C / min to 3°C / min, for example, 0.5°C / min, 1°C / min, 2°C / min, 2.5°C / min or 3°C / min, etc., not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0063] Preferably, the holding time of the annealing treatment is 1 h to 3 h, for example, 1 h, 1.5 h, 2 h, 2.5 h or 3 h, etc., and is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0064] Compared with the prior art, the present invention has the following beneficial effects:

[0065] (1) The present invention prepares a composite soft magnetic alloy magnetic powder by compounding nano-doped metal and micron ferroalloy powder under mild conditions. The magnetic powder core prepared using the composite soft magnetic alloy magnetic powder has high magnetic permeability and relatively low magnetic loss, better superposition effect, and good comprehensive performance.

[0066] (2) The magnetic core made of composite soft magnetic alloy powder prepared by the method of the present invention has a 50kHz magnetic permeability of more than 98, and a magnetic loss of 207W / cm at 50KHz and 100mT. 3 Within 50Oe, the effective magnetic permeability can reach more than 85%. DETAILED DESCRIPTION

[0067] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0068] Example 1

[0069] This embodiment provides a composite soft magnetic alloy powder, which is prepared by the following method:

[0070] (1) Weigh 100 g of iron-nickel powder with a particle size D50 of 2.5 μm, 0.2 g of colloidal copper and 20 g of acetone solution, stir and mix them evenly, dry them at 100° C., keep them warm for 10 min, and pass them through a 200-mesh sieve before performing a heat treatment in a N2 / H2 atmosphere at a heating rate of 0.5° C. / min to 800° C. for 1 h;

[0071] (2) The heat-treated composite magnetic powder is graded to screen out composite soft magnetic powder with a particle size D50 of 10 to 15 μm. 100 g of the composite magnetic powder is weighed, 0.2 g of phosphoric acid and 15 g of acetone are mixed evenly, and then dried at 120° C. and kept warm for 10 min. The mixture is sieved through a 120-mesh screen to obtain the composite soft magnetic alloy powder.

[0072] Example 2

[0073] This embodiment provides a composite soft magnetic alloy powder, which is prepared by the following method:

[0074] (1) Weigh 100 g of iron-nickel powder with a particle size D50 of 2 to 3 μm, 0.5 g of colloidal copper and 20 g of acetone solution by weight, stir and mix them evenly, dry them at 100° C., keep them warm for 10 min, and pass them through a 200-mesh sieve before performing a heat treatment in a N2 / H2 atmosphere at a heating rate of 0.5° C. / min to 780° C. for 1 h;

[0075] (2) The heat-treated composite magnetic powder is graded to screen out composite soft magnetic powder with a particle size D50 of 12 to 18 μm. 100 g of the composite magnetic powder is weighed, 0.4 g of phosphoric acid and 15 g of acetone are mixed evenly, and then dried at 120° C. and kept warm for 10 min. The mixture is sieved through a 120-mesh screen to obtain the composite soft magnetic alloy powder.

[0076] Example 3

[0077] This embodiment provides a composite soft magnetic alloy powder, which is prepared by the following method:

[0078] (1) Weigh 100 g of iron-nickel powder with a particle size D50 of 3 μm, 0.8 g of colloidal copper and 20 g of acetone solution, stir and mix them evenly, dry them at 100° C., keep them warm for 10 min, and pass them through a 200-mesh sieve before performing a heat treatment in a N2 / H2 atmosphere at a heating rate of 0.5° C. / min to 700° C. for 1 h;

[0079] (2) The heat-treated composite magnetic powder is graded to screen out composite soft magnetic powder with a particle size D50 of 15 to 22 μm. 100 g of the composite magnetic powder is weighed, 0.8 g of phosphoric acid and 15 g of acetone are mixed evenly, and then dried at 120° C. and kept warm for 10 min. The mixture is sieved through a 120-mesh screen to obtain the composite soft magnetic alloy powder.

[0080] Example 4

[0081] This embodiment provides a composite soft magnetic alloy powder, which is prepared by the following method:

[0082] (1) Weigh 100 g of iron-nickel powder with a particle size of D50 of 2 μm, 0.2 g of nano magnesium powder and 20 g of acetone solution by weight, stir and mix them evenly, dry them at 100° C., keep them warm for 10 min, and pass them through a 200-mesh sieve before performing a heat treatment in a N2 / H2 atmosphere at a heating rate of 0.5° C. / min to 660° C. for 1 h;

[0083] (2) The heat-treated composite magnetic powder is graded to screen out composite soft magnetic powder with a particle size D50 of 10 to 15 μm. 100 g of the composite magnetic powder is weighed, 0.1 g of phosphoric acid and 15 g of acetone are mixed evenly, and then dried at 120° C. and kept warm for 10 min. The mixture is sieved through a 120-mesh screen to obtain the composite soft magnetic alloy powder.

[0084] Example 5

[0085] This embodiment provides a composite soft magnetic alloy powder, which is prepared by the following method:

[0086] (1) Weigh 100 g of iron-nickel powder with a particle size of D50 of 2 μm, 0.8 g of nano magnesium powder and 20 g of acetone solution by weight, stir and mix them evenly, dry them at 100° C., keep them warm for 10 min, and pass them through a 200-mesh sieve before performing a heat treatment in a N2 / H2 atmosphere at a heating rate of 0.5° C. / min to 660° C. for 1 h;

[0087] (2) The heat-treated composite magnetic powder is graded to screen out composite soft magnetic powder with a particle size D50 of 10 to 15 μm. 100 g of the composite magnetic powder is weighed, 0.2 g of phosphoric acid and 15 g of acetone are mixed evenly, and then dried at 120° C. and kept warm for 10 min. The mixture is sieved through a 120-mesh screen to obtain the composite soft magnetic alloy powder.

[0088] Example 6

[0089] This embodiment provides a composite soft magnetic alloy powder, which is prepared by the following method:

[0090] (1) Weigh 100 g of iron-nickel powder with a particle size of D50 of 2.5 μm, 0.5 g of nano zinc and 20 g of acetone solution by weight, stir and mix them evenly, dry them at 100° C., keep them warm for 10 min, and pass them through a 200-mesh sieve before performing a heat treatment in a N2 / H2 atmosphere at a heating rate of 0.5° C. / min to 440° C. for 1 h;

[0091] (2) The heat-treated composite magnetic powder is graded to screen out composite soft magnetic powder with a particle size D50 of 10 to 15 μm. 100 g of the composite magnetic powder is weighed, 0.2 g of phosphoric acid and 15 g of acetone are mixed evenly, and then dried at 120° C. and kept warm for 10 min. The mixture is sieved through a 120-mesh screen to obtain the composite soft magnetic alloy powder.

[0092] Example 7

[0093] The only difference between this embodiment and embodiment 1 is that the mass of the colloidal copper is 2 g, and the other conditions and parameters are exactly the same as those in embodiment 1.

[0094] Example 8

[0095] The only difference between this embodiment and embodiment 1 is that the mass of the colloidal copper is 0.1 g, and the other conditions and parameters are exactly the same as those in embodiment 1.

[0096] Example 9

[0097] The only difference between this embodiment and embodiment 1 is that the mass of the passivating agent phosphoric acid is 0.05 g, and the other conditions and parameters are exactly the same as those in embodiment 1.

[0098] Example 10

[0099] The only difference between this embodiment and embodiment 1 is that the mass of the passivating agent phosphoric acid is 1 g, and the other conditions and parameters are exactly the same as those in embodiment 1.

[0100] Comparative Example 1

[0101] The only difference between this comparative example and Example 1 is that colloidal copper is not added, and other conditions and parameters are exactly the same as those in Example 1.

[0102] Comparative Example 2

[0103] The only difference between this comparative example and Example 1 is that the colloidal copper is replaced by elemental nano copper, the heat treatment temperature is 1084° C., and the other conditions and parameters are exactly the same as those in Example 1.

[0104] Comparative Example 3

[0105] The only difference between this comparative example and Example 1 is that phosphoric acid is not added for passivation treatment, and other conditions and parameters are exactly the same as those in Example 1.

[0106] Performance Test:

[0107] Weigh 100 g of the soft magnetic alloy powder obtained in the embodiment and the comparative example, mix them evenly with 1 g of coupling agent KH550 and 20 g of acetone, dry them at 100 ° C, and sieve them through 200 mesh; then add 1.5 g of epoxy resin and 10 g of acetone to the magnetic powder, dry them at room temperature, sieve them through 100 mesh, add 0.3 g of zinc stearate, and stir evenly; the powder is sieved at 10 T / cm 2 The magnetic ring was pressed into a magnetic ring by applying a pressure of 5s and maintaining the pressure; the magnetic ring was placed in N2 for annealing, the heating rate was 3℃ / min, the temperature was raised to 700℃, and the temperature was maintained for 1h to obtain the magnetic core. The magnetic permeability and loss of the magnetic core were tested by the instrument SY-8232-BH, and the superposition performance of the magnetic core was tested by the instrument WAYNEKREE6500B. The test results are shown in Table 1:

[0108] Table 1

[0109]

[0110]

[0111] As can be seen from Table 1, from Examples 1-6, the magnetic core made of the composite soft magnetic alloy powder prepared by the method of the present invention has a 50kHz magnetic permeability of more than 98, and a magnetic loss of 207W / cm at 50KHz and 100mT. 3 Within 50Oe, the effective magnetic permeability can reach more than 85%.

[0112] By comparing Example 1 and Examples 7-8, it can be seen that in the preparation process of the composite soft magnetic alloy powder of the present invention, the addition amount of the doping metal source will affect its performance. The mass ratio of the ferroalloy powder to the doping metal source is controlled at 100:(0.2-0.8), and the performance of the composite soft magnetic alloy powder is better. If the addition amount of the doping metal source is too low, the soft magnetic alloy powders cannot be fully combined, resulting in excessive hysteresis loss of the magnetic core. If the addition amount of the doping metal source is too high, the proportion of non-magnetic material in the soft magnetic alloy powder increases, which will cause the resistivity of the prepared magnetic core to decrease, thereby increasing the loss of the magnetic core.

[0113] By comparing Example 1 with Examples 9-10, it can be seen that during the preparation process of the composite soft magnetic alloy powder of the present invention, the amount of passivator added will affect its performance. By controlling the mass ratio of the composite material to the passivator at 100:(0.1-0.8), the performance of the composite soft magnetic alloy powder obtained is better. If the amount of passivator added is too low, a uniform passivation layer cannot be formed on the surface of the powder, and the resistance of the powder cannot be increased, resulting in excessively high core loss performance. If the amount of passivator added is too high, the proportion of non-magnetic substances in the magnetic powder is too high, resulting in a large decrease in the magnetic permeability of the prepared magnetic core.

[0114] From the comparison between Example 1 and Comparative Example 1, it can be seen that the present invention reduces the hysteresis loss and eddy current loss of the powder by doping metal, reduces the residual stress after pressing, and thus reduces the loss performance of the magnetic core.

[0115] From the comparison between Example 1 and Comparative Example 2, it can be seen that when single copper is used, the dispersion degree of the mixed magnetic powder is poor, and agglomeration is easily caused, which leads to a decrease in the resistivity of the magnetic powder.

[0116] By comparing Example 1 and Comparative Example 3, it can be seen that the present invention performs passivation treatment on the composite magnetic powder to passivate the doped metal source on the surface of part of the iron alloy powder, so that the composite soft magnetic alloy powder has high magnetic permeability, high frequency and low loss performance characteristics, higher DC superposition characteristics, and better mechanical strength.

[0117] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing a composite soft magnetic alloy powder, characterized in that: The preparation method comprises the following steps: (1) mixing an iron alloy powder, a doping metal source and a first solvent, performing a drying step to obtain a mixed dry material, and heat treating the mixed dry material to obtain a composite material; (2) mixing the composite material, the passivating agent and the second solvent, and performing a two-step drying process to obtain a composite soft magnetic alloy powder; Wherein, the doped metal source includes colloidal metal and / or metal element, and the melting point of the metal element is ≤800°C.

2. The preparation method according to claim 1, characterized in that The ferroalloy powder in step (1) comprises any one of iron-nickel alloy powder, iron-silicon alloy powder, iron-nickel-molybdenum alloy powder or iron-silicon-chromium alloy powder, or a combination of at least two thereof; Preferably, the median particle size D50 of the ferroalloy powder in step (1) is 1 μm to 3 μm; Preferably, in step (1), the first solvent comprises acetone and / or ethanol; Preferably, in step (1), the mass ratio of the ferroalloy powder, the doping metal source and the first solvent is 100:(0.2-0.8):20; Preferably, the colloidal metal comprises colloidal nickel and / or colloidal copper; Preferably, the metal element includes any one of elemental zinc, elemental aluminum or elemental magnesium, or a combination of at least two thereof; Preferably, the metal element is nanometer-scale metal element powder.

3. The preparation method according to claim 1 or 2, characterized in that: The temperature of the one-step drying treatment in step (1) is 100° C. to 150° C.; Preferably, the drying time in step (1) is 10 to 30 minutes; Preferably, the drying step in step (1) is followed by screening; Preferably, the mesh size of the sieve used in the sieving process in step (1) is 200 to 500 meshes.

4. The preparation method according to any one of claims 1 to 3, characterized in that: The temperature of the heat treatment in step (1) is greater than the melting point of the doping metal source; Preferably, the temperature of the heat treatment in step (1) is less than the melting point of the ferroalloy powder; Preferably, the atmosphere of the heat treatment in step (1) comprises nitrogen and / or hydrogen; Preferably, the heating rate of the heat treatment in step (1) is 0.5°C / min to 2°C / min; Preferably, the heat treatment in step (1) is carried out for a holding time of 1 to 3 hours.

5. The preparation method according to any one of claims 1 to 4, characterized in that: The median particle size D50 of the composite material in step (2) is 10 μm to 30 μm; Preferably, the passivating agent in step (2) comprises phosphoric acid and / or chromic acid; Preferably, the mass ratio of the composite material to the passivating agent in step (2) is 100:(0.1-0.8); Preferably, in step (2), the second solvent comprises acetone and / or ethanol.

6. The preparation method according to any one of claims 1 to 5, characterized in that: The temperature of the second step drying treatment in step (2) is 100-150° C. Preferably, the time for the second-step drying treatment in step (2) is 10 min to 30 min; Preferably, the two-step drying process in step (2) is followed by screening; Preferably, the mesh size of the sieve used in the sieving process in step (2) is 100 to 300 meshes.

7. A composite soft magnetic alloy powder, characterized in that: The composite soft magnetic alloy powder is prepared by the preparation method according to any one of claims 1 to 6.

8. A composite magnetic powder core, characterized in that: The composite magnetic powder core comprises the composite soft magnetic alloy powder as claimed in claim 7.

9. A method for preparing the composite magnetic powder core as claimed in claim 8, characterized in that: The preparation method comprises the following steps: The composite soft magnetic alloy powder as claimed in claim 7 is mixed with a coupling agent and then dried, the dried material is mixed with a binder and a release agent to obtain a mixed material, the mixed material is pressed to obtain a magnetic core blank, and the magnetic core blank is annealed to obtain the composite magnetic powder core.

10. The preparation method according to claim 9, characterized in that: The coupling agent includes a silane coupling agent and / or a titanate coupling agent; Preferably, the mass ratio of the composite soft magnetic alloy powder to the coupling agent is 100:(1-2); Preferably, the drying temperature is 80°C to 150°C; Preferably, the drying time is 10 min to 20 min; Preferably, a screening process is performed after the drying; Preferably, the mesh size of the sieve used in the one-time screening process is 100 to 300 meshes; Preferably, the adhesive comprises any one of epoxy resin, silicone resin or phenolic resin or a combination of at least two thereof; Preferably, based on the mass of the dried material being 100%, the amount of the binder added is 1.5% to 3%; Preferably, the release agent comprises any one of zinc stearate, barium stearate, aluminum stearate, talc or boron nitride, or a combination of at least two thereof; Preferably, based on the mass of the dried material being 100%, the added amount of the demoulding machine is 0.3% to 3%; Preferably, the mixed material is subjected to a secondary screening process; Preferably, the mesh size of the secondary screening process is 50-100 meshes; Preferably, the pressure of the pressing treatment is 9T / cm 2 ~20T / cm 2 ; Preferably, the holding time of the pressing process is 1s to 10s; Preferably, the atmosphere of the annealing treatment comprises nitrogen; Preferably, the annealing temperature is 500°C to 1100°C; Preferably, the heating rate of the annealing treatment is 0.5°C / min to 3°C / min; Preferably, the holding time of the annealing treatment is 1 h to 3 h.

Citation Information

Patent Citations

  • Magnetic metal powder which is of composite structure and used for preparing metal powder core

    CN103545074A

  • Fe / FeSi composite iron powder core with layered structure and preparation method of Fe / FeSi composite iron powder core

    CN114582616A

Cited By

  • Alloy soft magnetic powder for differential mode inductor and preparation process and application of alloy soft magnetic powder

    CN120998619A

  • Alloy soft magnetic powder for differential mode inductors, its preparation process and applications

    CN120998619B